2003
DOI: 10.1038/sj.leu.2402870
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of galectin-7 in murine lymphoma cells is associated with progression toward an aggressive phenotype

Abstract: We have previously shown that ICAM-1-deficient mice were resistant to lymphoma dissemination of intravenously injected 164T2 lymphoma cells. Highly aggressive variants of this cell line, however, could overcome this resistance. To discern the complex pattern of gene expression involved in the evolution of aggressiveness in lymphoma cells, we compared the transcriptome of 164T2 cells with that of their aggressive variants using cDNA arrays. We identified several genes that were differentially expressed in nonme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
1
47
0
3
Order By: Relevance
“…We found that the most prominent change among the genes tested was the strong upregulation of galectin-7 (9). Specifically, we reported that galectin-7 was constitutively expressed in aggressive T lymphoma cells at both mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We found that the most prominent change among the genes tested was the strong upregulation of galectin-7 (9). Specifically, we reported that galectin-7 was constitutively expressed in aggressive T lymphoma cells at both mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 79%
“…We have previously shown that aggressive T lymphoma cells, but not their nonaggressive parental cells, expressed galectin-7 at the protein level (9), suggesting that galectin-7 may have a role in tumorigenesis. To test this hypothesis, we thus transduced the nonaggressive 267 T lymphoma cells with murine galectin-7 cDNA.…”
Section: Resultsmentioning
confidence: 99%
“…Des calculs de vitesse de migration réa-lisés lors de la fermeture de blessures montrent que les cellules exprimant la toxine tétanique (TeNT) sauvage ont une vitesse de migration réduite de moitié par rapport aux cellules exprimant une forme mutée de la toxine tétanique. La cellubrévine joue donc un rôle important dans la migration cellulaire [3]. L'équipe de M.G.…”
unclassified
“…Les cellules en migration, en bordure de blessure, exprimant la TeNT mutante, contrairement à celles exprimant la TeNT sauvage, internalisent un anticorps anti-β1-intégrine. Dans ces cellules, la Cb colocalise avec la β1-intégrine endocytée [3]. La Cb joue donc un rôle important dans la migration cellulaire en régulant l'adhérence des cellules au substrat médiée par la β1-intégrine.…”
unclassified
See 1 more Smart Citation